2019
DOI: 10.1155/2019/7658594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Intensity of Soil-Transmitted Helminths, and Factors Associated with Infection: Importance in Control Program with Ivermectin and Albendazole in Eastern Côte d’Ivoire

Abstract: Evaluation of soil-transmitted helminths (STHs) and implementation of additional interventions are required in the region of a filariasis control program, given that antifilariasis drugs also have a beneficial effect on STHs. Thus, this study determines the extensive epidemiology of STHs to improve their successful control. Stool samples were analyzed using the Kato-Katz method. Chi-squared and Kruskal-Wallis tests were used to measure differences in infection rates and intensities, respectively, and logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
5
8
0
Order By: Relevance
“…This is in tandem with Mwandawiro et al's [ 11 ] survey in selected counties within Kenya, which showed a significant reduction of STH and schistosomes after repeated observation from 2012 to 2017. Ascaris lumbricoides was the most predominant etiological agent in this assessment which agrees with other researchers [ 7 , 17 , 18 ]; however, it disagrees with Halliday et al [ 19 ] and Loukouri et al [ 18 ] who recorded lower prevalence of A. lumbricoides in South coastal Kenya. Sang et al [ 20 ] recorded a lower prevalence of A. lumbricoides in their assessment at South Nyanza Kisumu.…”
Section: Discussionsupporting
confidence: 71%
“…This is in tandem with Mwandawiro et al's [ 11 ] survey in selected counties within Kenya, which showed a significant reduction of STH and schistosomes after repeated observation from 2012 to 2017. Ascaris lumbricoides was the most predominant etiological agent in this assessment which agrees with other researchers [ 7 , 17 , 18 ]; however, it disagrees with Halliday et al [ 19 ] and Loukouri et al [ 18 ] who recorded lower prevalence of A. lumbricoides in South coastal Kenya. Sang et al [ 20 ] recorded a lower prevalence of A. lumbricoides in their assessment at South Nyanza Kisumu.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, Njunda et al [11] in Yaounde, the political capital of Cameroon and Tabi et al [12] in Tiko town, South West Region of Cameroon, found lower prevalences (2.5% and 1% respectively) than we did. A much higher prevalence of 19.3% has been reported among children in three communities of Dschang town by Fusi-Ngwa et al [13] and in other regions of Africa [14,15]. Differences in prevalence between studies vary in relation to geographical areas, and climatic conditions as earlier observed by Ratard et al [16].…”
Section: Discussionmentioning
confidence: 77%
“…It remains unknown why the prevalence of hookworms and T. trichiura were lower in the present study as the studied localities share the same climate. However, as we used the Willis technique which has lower sensitivity than Kato-Katz quantitative technique [20], which was used by Nkengazong et al [17], Fusi-Ngwa et al [13] and by Loukouri et al [15], this may partly explain the observed differences. The higher prevalence of Ascaris may be related to their thick shell, which seems to improve their preservation through time compared to other STHs [21] and renders them remarkably resistant to harsh environmental conditions.…”
Section: Discussionmentioning
confidence: 91%
“…It has to be considered that we did not repeat STH testing of infected individuals 2-4 weeks after treatment to assess cure and egg reduction rates. Barriers that could prevent individuals to be continuously included in parasitological survey would be the absence from the village, misunderstanding, and lack of information [40]. However, our study was not designed to assess drug efficacy, but to measure impact of an intervention (MDA for LF and onchocerciasis), and cross-sectional sampling was sufficient for this purpose.…”
Section: Not Adjusted For Baseline Prevalence Adjusted For Baseline Pmentioning
confidence: 99%